P223 Once-daily low-dose indacaterol/mometasone via breezhaler® reduces exacerbations in patients with inadequately controlled asthma: phase III QUARTZ study. (12th November 2019) - Kornmann, O; Mucsi, J; Kolosa, N; Bandelli, L; Satlin, LC; Sen, B; D'Andrea, P
Abstract : Introduction: GINA 2019 recommends LABA/ICS as preferred controller therapy in patients with inadequately controlled asthma despite low-dose ICS treatment. This Phase-III study (NCT02892344 ; the QUARTZ Study) is part of the PLATINUM clinical program which supports the development of both indacaterol acetate/mometasone furoate (IND/MF) and indacaterol acetate, glycopyrronium bromide and mometasone furoate (IND/GLY/MF). Specifically, in QUARTZ we evaluated efficacy and safety of low-dose IND/MF 150/80 µg once daily (o.d.) via Breezhaler ® versus MF 200 µg o.d. via Twisthaler ® in symptomatic asthma patients, both adults and adolescents. IND/MF demonstrated significant improvements in trough FEV1 and ACQ-7 in these patients. Here, we present exacerbation data, a secondary endpoint from QUARTZ study. Methods: This Phase III, 12-week, double-blind study randomised (1:1) asthma patients (≥12yrs) receiving low-dose ICS (with or without additional controller medication) prior to study, to IND/MF or MF (Figure) . Patients were symptomatic (ACQ-7 ≥1.5) prior to randomisation and were not required to have a history of exacerbations prior to the study. The rate and time-to-first moderate-to-severe and all exacerbations (mild, moderate and severe) were evaluated as secondary endpoints comparing IND/MF versus MF. Safety was assessed. Results: Of 802 patients randomised, 768 completed the study. Lower rates of moderate-to-severe [Rate ratio (RR) 0.25, 95% CI: 0.12, 0.52] and all exacerbations (RR: 0.30, 95% CI: 0.18, 0.50) were observed in IND/MF versus MF. Further IND/MF treatment, delayed time-to-first exacerbation vs MF for moderate-to-severe (Hazard ratio (HR): 0.29, 95% CI: 0.14, 0.59), and all asthma exacerbations (HR: 0.30, 95% CI: 0.18, 0.50). Safety was comparable between the two groups. Conclusion: In symptomatic asthma patients, IND/MF showed greater effect on reducing rate (75% of moderate-to-severe and 70% of all exacerbations) and time-to-first exacerbations vs MF. The result was apparent even in patients with a low history of exacerbations. These results demonstrate additive benefit of IND in a fixed combination with MF in terms of reduction in exacerbations and supports the use of IND/MF as efficacious maintenance therapy for asthma versus MF alone.